Profiling ESP Students’ Needs as Recommendation for Designing Hospitality Syllabus in Indonesian Vocational Schools - Ma'fiyah, Imroatul (FOSTER: Journal of English Language Teaching, 2023)
This descriptive qualitative study examines the needs of ESP students’ as a fundamental basis for designing an English for hotel program in the context of vocational secondary school in Indonesia. English teachers and students from hospitality program collaborated to investigate learners’ specific needs, which were then used to make recommendations for classroom implementation and instruction. The study aimed to understand how students in the hospitality program perceive their English needs and assess the adequacy of the current syllabus in meeting those needs. The findings revealed that students identified a range of language skills they need to acquire, including speaking, listening, reading and writing skills with particular emphasis on communication in hotel costumer service situations. Students expressed their expectations for practical, interactive and industry-relevant language learning experiences. The study emphasizes the importance of incorporating materials and real-world scenarios into syllabus to enhance students’ language proficiency and job readiness. The research findings serve as a valuable contribution to reorganizing the syllabus to better align with the students’ needs. Further research is recommended to explore the significance of addressing students’ specific needs as language learners and in relation to their career goals in the hotel industry.